2002
DOI: 10.1038/ng940
|View full text |Cite
|
Sign up to set email alerts
|

Selection for short introns in highly expressed genes

Abstract: Transcription is a slow and expensive process: in eukaryotes, approximately 20 nucleotides can be transcribed per second at the expense of at least two ATP molecules per nucleotide. Thus, at least for highly expressed genes, transcription of long introns, which are particularly common in mammals, is costly. Using data on the expression of genes that encode proteins in Caenorhabditis elegans and Homo sapiens, we show that introns in highly expressed genes are substantially shorter than those in genes that are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
400
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 475 publications
(442 citation statements)
references
References 29 publications
37
400
4
1
Order By: Relevance
“…Previously [8], the high abundance of a certain gene in EST libraries was an indication the gene was highly expressed in the human body. It was pointed out [8], however, that this method is prone to bias due to the inclusion of normalized and tumor libraries and overrepresentation of certain tissues. Our approach overcomes this difficulty and confirms the previous result.…”
Section: Length Analysis Of Hk Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously [8], the high abundance of a certain gene in EST libraries was an indication the gene was highly expressed in the human body. It was pointed out [8], however, that this method is prone to bias due to the inclusion of normalized and tumor libraries and overrepresentation of certain tissues. Our approach overcomes this difficulty and confirms the previous result.…”
Section: Length Analysis Of Hk Genesmentioning
confidence: 99%
“…The more copies of a gene required for the organism, the stronger this pressure should be. The first demonstration of this principle [8] showed that genes with a large number of expressed sequence tags (ESTs) in public libraries (and hence most mRNAs) have a significantly shorter average intron length than those with fewer ESTs.Here, an implication of this principle is used to validate a set of HK genes. The HK genes, which are transcribed in all somatic cells and under all circumstances, are by nature highly expressed, and therefore should be selected to have shorter introns.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, while highly expressed genes were found to be shorter in animals and to harbor fewer and shorter introns [30], they appear least compact and relatively largest in plants [33] and C. elegans [29]. Several evolutionary scenarios such as selection for economy and genomic design have been discussed to explain the observed trends [31,34].…”
Section: Multistimuli Response Genes Are Shorter In Arabidopsismentioning
confidence: 99%
“…The correlation between expression level and gene size and associated properties such as number and length of introns has been investigated in several studies [28][29][30][31][32][33][34]. Surprisingly, while highly expressed genes were found to be shorter in animals and to harbor fewer and shorter introns [30], they appear least compact and relatively largest in plants [33] and C. elegans [29].…”
Section: Multistimuli Response Genes Are Shorter In Arabidopsismentioning
confidence: 99%